The Influence of Price and Product Quality on Purchasing Decisions at Raida Snack & Cookies, Sukabumi Regency - Ipah Masripah; Rully Moch. Ichsan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study was carried out in Sukabumi Regency's Raida Snack & Cookies. We at Raida Snack & Cookies in Sukabumi Regency are interested in learning how much of an influence consumers' purchasing decisions are made by price and product quality. This study uses associative qualitative analysis as its research methodology. Using the Yamane formula and a straightforward random sample process, 189 consumers of Raida Snack & Cookies in Sukabumi Regency were chosen at random to participate in this study. The first stage in performing an effect analysis is applying tests for validity, reliability, and classical assumptions to the research instrument. You can next test your hypotheses by using methods such as t-tests, coefficients of determination, and linear multiple regression. The association's investigation's findings indicate that there is a strong exchanges between price and purchasing decisions (r=0.669, or 66.9%), product quality and purchasing decisions (r=0.751, or 75.1%), and the interval between these two variables is 0.60–0.799, indicating a solid relationship. With a R Squared value of 71.8%, the determination analysis reveals that product price and quality significantly impact purchasing decisions; other variables, not considered in this study, account for the remaining 28.2%